Fecal microbiota transplantation for ulcerative colitis—where to from here? - Borody, Thomas J.; Clancy, Annabel (Translational Gastroenterology and Hepatology; Vol 4 (June 2019): Translational Gastroenterology and Hepatology, 2019)
Ulcerative colitis (UC) is one of several chronic inflammatory bowel diseases (IBD) characterised by intermittent exacerbations and remission of inflammation symptoms and the progressive development of complications over the course of the disease. Most current therapies focus on the suppression of inflammation, addressing the aberrant immune response aspect of UC. However, such inflammation-directed therapies are met with increasing concerns by both physicians and patients who do not perceive a long term solution in biologics but rather increased risk of serious infection, malignancy, high costs and significant loss of response (1).